REGENERATIVE STRATEGIES FOR SPORTS-RELATED MUSCULOSKELETAL INJURIES: FROM PRP TO 3D BIOPRINTING - Katarzyna Szlachetka; Aleksandra Gralec; Piotr Helbin (International Journal of Innovative Technologies in Social Science, 2026)
Regenerative medicine is becoming an increasingly important part of sports medicine, especially in the treatment of musculoskeletal injuries that are difficult to manage with conventional methods alone. This review provides a structured and clinically focused overview of established and emerging regenerative therapies used in sports-related musculoskeletal conditions. Particular attention is given to platelet-rich plasma (PRP), mesenchymal stem cells (MSCs), exosome-based therapies, low-intensity pulsed ultrasound (LIPUS), hydrogel-based scaffolds, bone marrow aspirate concentrate, adipose-derived biologics, and three-dimensional (3D) bioprinting. A structured narrative review with scoping characteristics was conducted in accordance with PRISMA-ScR recommendations. Articles published between 2003 and 2025 were identified through PubMed, Scopus, Web of Science, and Google Scholar, with priority given to studies relevant to clinical practice, rehabilitation, functional outcomes, and athlete-centered recovery. The reviewed evidence suggests that PRP and MSC-based therapies currently represent the main biologic approaches in this field, while newer technologies offer promising but still largely experimental directions for future treatment. The value of regenerative therapies extends beyond tissue repair alone and may also influence rehabilitation, return-to-play, and quality of life. At the same time, their clinical use remains limited by methodological heterogeneity, lack of standardization, and insufficient long-term data. Further high-quality studies are needed to define clear indications, improve treatment protocols, and support the evidence-based integration of regenerative therapies into modern sports medicine.